Maternal circulating syncytiotrophoblast-derived extracellular vesicles contain biologically active 5'-tRNA halves - Cooke, W; Cribbs, A; Zhang, W; Kandzija, N; Motta-Mejia, C; Dombi, E; Ri, R; Cerdeira, A; Redman, C; Vatish, M (Elsevier, 2019)
The placenta releases syncytiotrophoblast-derived extracellular vesicles (STB-EV) into the maternal circulation throughout gestation. STB-EV dependent signalling is believed to contribute to the widespread maternal adaptive physiological changes seen in pregnancy. Transfer RNA (tRNA) halves have been identified in vesicles released from other human and murine organ systems, which alter gene expression in target cells. Here, we characterise tRNA-half expression in STB-EV and demonstrate biological activity of a highly abundant tRNA-half. Short RNA from ex-vivo, dual-lobe placental perfusion STB-EV was sequenced, showing that most (>95%) comprised tRNA species. Whole placental tissue contained <50% tRNA species, suggesting selective packaging and export of tRNA into STB-EV. Most tRNA within STB-EV were 5'-tRNA halves cleaved at 30-32 nucleotides. The pattern of tRNA expression differed depending on the size/origin of the STB-EV; this was confirmed by qPCR. Protein synthesis was suppressed in human fibroblasts when they were cultured with a 5'-tRNA half identified from STB-EV sequencing. This study is the first to evaluate tRNA species in STB-EV. The presence of biologically active 5'-tRNA halves, specific to a vesicular origin, suggests a novel mechanism for maternal-fetal signalling in normal pregnancy.